Multiple milia formation in blistering diseases - Aikaterini Patsatsi, MD, PhD; Cybill Dianne C. Uy, MD; Dedee F. Murrell, MD, PhD (Wolters Kluwer, 2020)
Background: Milia are superficial keratinous cysts seen as pearly white, dome-shaped lesions 1-2 mm in diameter. Milia are associated with diseases that cause subepidermal blistering, such as hereditary forms of epidermolysis bullosa, epidermolysis bullosa acquisita, bullous pemphigoid, bullous lichen planus, and porphyria cutanea tarda. Multiple eruptive milia are rare and more extensive in number than primary milia. Objective: The aim of this study was to search the literature for cases of blistering diseases with multiple milia formation, especially in areas of the skin where there was no evidence of blistering or trauma, and review the interpretations of their pathogenesis. Methods: We performed a literature search with the terms multiple milia and bullous diseases, pemphigoid, and pemphigus. Results: Very few studies have investigated the origin of milia. Primary milia are thought to originate from the sebaceous collar of vellus hairs, and secondary milia are believed to derive from eccrine ducts more commonly than from overlying epidermis, hair follicles, or sebaceous ducts. Milia secondary to blisters or trauma are speculated to be produced through the regeneration process of disrupted sweat glands or hair follicles. Immunological predisposition, aberrant interaction between the hemidesmosomes, and the extracellular matrix components beneath the hemidesmosomes have been described with regard to the formation of numerous milia during recovery. Multiple milia could be a primary manifestation of dystrophic epidermolysis bullosa in skin areas without evidence of blistering. Conclusion: The exact etiology of multiple milia remains unknown. Immunological predisposition and improper interaction between hemidesmosomes and extracellular matrix components are speculated to play a role in the formation of milia during recovery of bullous lesions in blistering diseases. Still, further studies on the triggering mechanisms of keratinocyte dysfunction in cases of multiple milia formation without evidence of prior blistering are needed.